Analysis of forest cover in Parque Nacional Tingo María (Peru) using the random forest algorithm - Puerta, Ronald (2023)
The establishment of natural protected areas is one of the most effective strategies to conserve forests and their biodiversity; however, the uncontrolled advance of deforestation resulting from the change of use to expand the agricultural frontier has become a threat to these intangible areas. This research aimed to analyze the dynamics of forest cover in Parque Nacional Tingo María (PNTM) and its buffer zone (ZA) located in the high jungle of the Huánuco region of Peru. The main input was Sentinel-2 images that were classified using the Random Forest algorithm. As a result, coverage maps were obtained for the study area corresponding to the years 2017, 2019, 2021 and 2023, achieving considerable thematic accuracy. During the evaluation periods, the rates of change from forest to non-forest within the PNTM presented low values -0.26% (2017 - 2019); -1.24% (2019 - 2021) and -0.02% (2021 - 2023). While the forests in the ZA have undergone a dynamic transition, with rates of change of -2.97%; -4.39% and -1.15% derived from land use change. The landscape metrics suggest that the forests of the PNTM are moderately fragmented, and the forests of the ZA are strongly fragmented, which leads to the conclusion that the protected natural area has fulfilled its objective of maintaining vegetation cover.